New model of electronic health record: Macedonian case study - Gavrilov, Goce; Trajkovik, Vladimir (FICT, 2016)
. Electronic Health Record (EHR) systems are core applications in any e-Health environment and represent basic services for healthcare information technology platforms. Many EHR introduction projects ran into trouble because of the inappropriate model and concept of implementation, according to the requirements and standards, as well as the lack of the acceptance of the EHR related services among physicians. The aim of this paper is to give a brief overview of the current situation of citizens’ healthcare data and need for the nationwide EHR with focus on R. Macedonia. We are making an analysis of the best practices of EHR's implementation and introduction in many countries in the world. We use these positive and useful experiences in the Macedonian case of EHR's introduction and propose a new collaborative model of EHR for healthcare organizations, adapted to the situation and needs of the Macedonian healthcare information system.
Keywords: Electronic health record (EHR), e- services, healthcare, collaboration